Experimental studies of a machine for collecting the Colorado potato beetle - P. V. Zayats; P. P. Kazakevich (Аграрная наука Евро-Северо-Востока, 2021)
ional Academy of Sciences of Belarus, Minsk, the Republic of Belarus The substantiation of the design and technological scheme of the machine for the mechanical collection of the Colorado potato beetle in the production of environmentally friendly potato is carried out. The parameters and modes of rotors with flexible-elastic blades and regulators of the amplitude of their oscillations, providing high-quality shaking and collection of Colorado potato beetle individuals from the tops with minimal damage, have been experimentally substantiated. A description of the laboratory installation, an experimental sample of a combined unit is presented, and a methodology for conducting experiments is described. Experimental studies were carried out in 2004-2008 in the experimental field of the Educational institution "Grodno State Agrarian University" (UO "GGAU") and in the fields of the Agricultural production cooperative (SEC) "Zanemansky" of the Mostovsky dis-trict of the Grodno region. It was found that in order to reduce the energy intensity of the process, the interaction of the rotor with the tops in its apical part, where the maximum con-centration of Colorado potato beetle individuals takes place, is expedient. The minimum amount of beetle on the tops and the absence of visible damage to it are achieved when the diameter of the nylon threads of the blade is 1.2-1.5 mm, and the rational position of the regulator from the rotor axis is 0.14-0.18 m according to the energy intensity condition. Under the condition of minimal energy consumption of the process and without visible damage to the leaves, the circumferential speed range of the rotor should be 3-4 m/s. A regression equation of the second degree is obtained, which determines the relationship of the residual number of beetle individuals on the tops after the passage of the machine with the circumferential speed of the rotor Voc, the position of the regulator on the radius of the rotor Rr and the cross section of the blade Sbl. The optimal values were determined by solving the equation: Voc = 3.7 m/s, Rr = 0.16 m, Sbl = 1800 mm2 .